Methodology for assessing threshold indicators of f inancial security of the Republic of Belarus - Polonik, Stepan S.; Smolyarova, Marina A. (Journal of the Belarusian State University. Economics, 2019)
The scientif ic article has developed approaches to the formation of the f inancial security strategy of the Republic of Belarus. Indicators of f inancial security of the republic, internal and external threats to the f inancial security of the state, price indicators reflecting the processes and condition of f inancial markets are determined.